Photodynamic Therapy: Porous Porphyrin‐Based Organosilica Nanoparticles for NIR Two‐Photon Photodynamic Therapy and Gene Delivery in Zebrafish (Adv. Funct. Mater. 21/2018). (May 2018) - Mauriello Jimenez, Chiara; Aggad, Dina; Croissant, Jonas G.; Tresfield, Karen; Laurencin, Danielle; Berthomieu, Dorothée; Cubedo, Nicolas; Rossel, Mireille; Alsaiari, Shahad; Anjum, Dalaver H.; Sougrat, Rachid; Roldan‐Gutierrez, Manuel A.; et al.
Abstract : Porphyrin‐based mesoporous organosilica nanoparticles are designed by Nadir Bettache, Jean‐Olivier Durand, and co‐workers in article number1800235 . These nanoparticles possess a high specific surface area and large mesopores of 10–80 nm diameters. Two‐photon photodynamic therapy of breast cancer and siRNA delivery were both performed in zebrafish embryos and were very efficient.